Preventing Foodborne Illness: Yersiniosis - Aswathy Sreedharan; Correy Jones; Keith R. Schneider (EDIS)
Yersiniosis is an infectious disease caused by the consumption of food contaminated with the bacterium Yersinia. It is characterized by gastroenteritis, with diarrhea and/or vomiting, fever, abdominal pains, and skin rashes. Although outbreaks of yersiniosis are uncommon and sporadic in nature, foodborne outbreaks have been associated with consumption of contaminated food or water, and in places of high pork consumption. This 3-page fact sheet was written by Aswathy Sreedharan, Correy Jones, and Keith Schneider, and published by the UF Department of Food Science and Human Nutrition, June 2012.